US Military Power and Interests in Asia-Pacific: The Challenges to Human Security and Development - Journal, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 19 No 1 (2004): Human Security in Conflict Situations, 2007)
Proceedings on the forum "US military power and interests in Asia-Pacific: The challenges to human security and development."
Keywords: US, Military Power, Asia-Pacific, Human Security, Development